Perbandingan Tingkat Pertumbuhan Ekonomi Amerika Serikat, Perancis, Jepang, Singapura, India, dan China - Kresnawati, Megahnanda Alidyan (Global and Policy Journal of International Relations, 2013)
ABSTRACTA country's economic growth is an important factor that could determine whether the country is a first world, second world, or third world. Therefore there are some variables that can be used to measure the growth of the economy, Gross Domestic Product (GDP), trust on the performance government and political system, the poverty, and population growth level. This paper will analyse about some first world and second world country with method of difference combined with most difference system design.Keywords: economic growth, Gross Domestic Product (GDP), political system, the poverty, population growth level.DOI:https://doi.org/10.33005/jgp.v1i01.2008